THE RESOURCE-BASED VIEW (RBV) APPROACH AS THE MAIN FOUNDATION FOR ACHIEVING SUSTAINABLE COMPETITIVE ADVANTAGE THROUGH THE VRIO FRAMEWORK: DONA ELVIA DESI - Elvia Desi, Dona (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
In an uncertain environment, and increasingly high levels of competition, the competitive advantage of business organizations is becoming shorter and more difficult to maintain. Facing this situation, a strategy is needed in an effort to maintain competitive advantage in a sustainable manner. One effort that can be made is through technological capabilities and dynamic capabilities in managing the resources owned. One approach that can be applied by companies to face various challenges and opportunities is an approach based on the resources-based view (RBV). This study aims to determine the extent to which the RBV concept plays a role in providing solutions to the company's efforts to maintain its competitive advantage in a sustainable manner. Through the VRIO framework. The method used in this paper is a literature study, namely by reviewing reading sources related to the concept of competitive advantage through the RBV approach. Based on the results of the study, a company will generally have the ability above the performance of its competitors if it is able to apply the RBV concept. This is because the company is more focused on identifying and managing the potential resources (tangible and intangible) it has, so that it has a competitive advantage in the long term.